A relationship between salivary stress hormones and perceived mood state during the competition period in speed skaters - Nakamura, M.; Kon, M.; Iizuka, T.; Ohiwa, N.; Yuda, J.; Aoyanagi, T.; Takahashi, H. (Asian Conference on sport science. Sport science and elite training programme for world class performance. 25-26 October 2013. Hong Kong Sports Institute, Hong Kong, China, 2013)
As athletes are exposed to intense physical and psychological stress during competition season, it might be essential for the athletes to monitor and evaluate their daily change in physical condition. We investigated the relationship between salivary stress hormones (cortisol and dehydroepiandrosterone sulfate (DHEAS)) and perceived during a competition season in speed skaters.Nine speed skaters volunteered to participate in the study. Saliva samples and perceived data were collected every morning for consecutive days, from 3 days before the opening of four major competitions to the last day of the competition.Salivary secretary cortisol and DHEAS concentration were measured by enzyme-linked immunoassay (ELISA).The change in the perceived training load was significant changed during the competition period. The changes in cortisol and DHEAS/cortisol ratio during the competition period were observed. These results suggest that the daily changes in salivary stress hormones reflect the perceived physical condition in speed skaters. Using non-invasive salivary stress hormones would be an efficient tool for monitoring physical condition in athletes